2021
DOI: 10.1038/s41467-021-23155-3
|View full text |Cite
|
Sign up to set email alerts
|

Artificial dual solid-electrolyte interfaces based on in situ organothiol transformation in lithium sulfur battery

Abstract: The interfacial instability of the lithium-metal anode and shuttling of lithium polysulfides in lithium-sulfur (Li-S) batteries hinder the commercial application. Herein, we report a bifunctional electrolyte additive, i.e., 1,3,5-benzenetrithiol (BTT), which is used to construct solid-electrolyte interfaces (SEIs) on both electrodes from in situ organothiol transformation. BTT reacts with lithium metal to form lithium 1,3,5-benzenetrithiolate depositing on the anode surface, enabling reversible lithium deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 61 publications
1
146
0
Order By: Relevance
“…Several electrolyte‐based methods have been suggested to act as not only a cathodic redox mediator but also to form a protective layer on the anode. [ 25,26 ] Gu et al. reported carbon disulfide (CS 2 ) as an electrolyte additive that can react with polysulfides and induce the formation of thiosulfate‐containing protective layers on both the anode and cathode.…”
Section: Introductionmentioning
confidence: 99%
“…Several electrolyte‐based methods have been suggested to act as not only a cathodic redox mediator but also to form a protective layer on the anode. [ 25,26 ] Gu et al. reported carbon disulfide (CS 2 ) as an electrolyte additive that can react with polysulfides and induce the formation of thiosulfate‐containing protective layers on both the anode and cathode.…”
Section: Introductionmentioning
confidence: 99%
“…Irregular voids left in the BTT–Li interface layer during exchange reaction were filled by LiF particles from the electrolyte decomposition, forming an even and compact organic/ inorganic protective layer. [ 186 ] Another additive, thionyl chloride (SOCl 2 ), can react with Li anode spontaneously to establish dual‐functions LiCl‐rich surface film (Figure 12c–e ). The generated S from the redox reaction provides extra capacity and another product Li 2 SO 3 contributes to densifying the SEI layer to prohibit the shuttle of LiPSs.…”
Section: Strategies For Polysulfides Shuttle Inhibition Along the Shu...mentioning
confidence: 99%
“…Guo et al reported organothiol as a functional electrolyte additive which has thiol groups. [ 43 ] The thiol groups can react with Li metal and elemental sulfur (Figure 9c ), and construct functional layers. 1,3,5‐Benzenetrithiol (BTT) with the symmetrical sulfhydryl groups on the benzene ring is a typical organothiol.…”
Section: Organosulfur Additives In Li‐s Batteriesmentioning
confidence: 99%
“…Reproduced with permission. [ 43 ] Copyright 2021, Nature Publishing Group. e) Redox reaction processes of the Li‐S battery with BTT electrolyte.…”
Section: Organosulfur Additives In Li‐s Batteriesmentioning
confidence: 99%
See 1 more Smart Citation